2001
DOI: 10.1097/00001756-200112040-00049
|View full text |Cite
|
Sign up to set email alerts
|

Sound alters visual evoked potentials in humans

Abstract: When a single flash is accompanied by two auditory beeps, the single flash is perceived as two flashes. We investigated whether this crossmodal influence on visual perception occurs at the level of the modality-specific visual pathway or later. We compared the visual evoked potentials (VEPs) in the presence and absence of sound. Activity was modulated extensively and with short latency in trials in which an illusory flash was perceived. In addition, the brain potentials for the illusory flash were qualitativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
119
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(142 citation statements)
references
References 6 publications
21
119
2
Order By: Relevance
“…The ERP correlates of illusory and real flash perception have been compared previously (Shams et al, 2001) using three recording channels over occipital cortex. Both the illusory and real flash difference waveforms were reported to display a positive deflection at ϳ200 ms, which was interpreted as a common neural basis for the illusory and real percepts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ERP correlates of illusory and real flash perception have been compared previously (Shams et al, 2001) using three recording channels over occipital cortex. Both the illusory and real flash difference waveforms were reported to display a positive deflection at ϳ200 ms, which was interpreted as a common neural basis for the illusory and real percepts.…”
Section: Discussionmentioning
confidence: 99%
“…Previous ERP/magnetoencephalographic (Shams et al, 2001(Shams et al, , 2005aArden et al, 2003) and functional magnetic resonance (fMRI) investigations (Watkins et al, 2006) of the neural basis of the double-flash illusion have suggested that visual cortex activation underlies the perception of the illusory second flash. However, the exact timing of this visual cortex activity and the participation of other brain regions in engendering the illusion still remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…If that is the case, we would expect familiar and unfamiliar objects to be processed differently in the context of the sound-induced flash illusion. The sound-induced flash illusion represents a good way to test the role of visual familiarity in early audio-visual interactions because the illusion originates early in the processing stream [21,27,30,35] and because audition, not vision, dominates in this task [28][29].…”
Section: Page 5 Of 21mentioning
confidence: 99%
“…In this circumstance participants tend to perceive two visual stimuli instead of one, due to the higher reliability of audition compared to vision in tasks requiring rapid temporal discrimination [1]. The illusion constitutes a robust phenomenological perception [20] that has been ascribed to early cross-sensory interactions [21,27,30,35].…”
Section: Introductionmentioning
confidence: 99%
“…Sounds (short transient beeps) are presented concurrently with the visual flashes and evoke additional, illusory flashes; the number of presented beeps influences the number of flashes perceived (Shams et al, 2000). EEG activity measured during the task has shown that the perception of illusory flashes concurs with increased early EEG activity above the visual cortex (Shams, Kamitani, Thompson, & Shimojo, 2001) indicating auditoryvisual integration at a low, sensory, level. Additional evidence comes from a study by Arden, Wolf, and Messiter (2003), who showed that sound alone does not drive primary visual cortex (V1), yet the combination of the auditory and visual stimuli triggers additional activity in V1, which may drive the illusion.…”
mentioning
confidence: 99%